2016
DOI: 10.1371/journal.pone.0168089
|View full text |Cite
|
Sign up to set email alerts
|

Two Isoforms of Yersinia pestis Plasminogen Activator Pla: Intraspecies Distribution, Intrinsic Disorder Propensity, and Contribution to Virulence

Abstract: It has been shown previously that several endemic Y. pestis isolates with limited virulence contained the I259 isoform of the outer membrane protease Pla, while the epidemic highly virulent strains possessed only the T259 Pla isoform. Our sequence analysis of the pla gene from 118 Y. pestis subsp. microtus strains revealed that the I259 isoform was present exclusively in the endemic strains providing a convictive evidence of more ancestral origin of this isoform. Analysis of the effects of the I259T polymorphi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 96 publications
0
6
0
Order By: Relevance
“…Nevertheless, only Pla can convert plasminogen to plasmin by limited proteolysis, and this activity was likely crucial for the increased lethality of Y . pestis that developed during the course of evolution [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, only Pla can convert plasminogen to plasmin by limited proteolysis, and this activity was likely crucial for the increased lethality of Y . pestis that developed during the course of evolution [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular model was suggested that H-R substitution might have functional implications that result in better fitness for the R variant, thus contributing to the successful spread and high virulence of the USA300 strain [58]. The epidemic highly virulent Yersinia pestis strains possessed only the Pla T259 isoform of the plasminogen activator Pla while Pla I259 isoform is spread among Y. pestis isolates with limited virulence [60,61]. Computational and experimental analysis demonstrated that the Pla isoform found in Y .…”
Section: Discussionmentioning
confidence: 99%
“…Computational and experimental analysis demonstrated that the Pla isoform found in Y . pestis epidemic strains is more functionally efficient than that of the low virulent strains [61,62],…”
Section: Discussionmentioning
confidence: 99%
“…Here, we explored omptins representing a family of outer membrane proteases that have been identified in all major enterobacterial species pathogenic to humans [24] for the presence of similar immuno-reactive epitopes. The model pro-omptin antigen, Y. pestis Pla, was chosen for the following reasons: (i) the antigen is a surface-located outer-membrane integral protease with high similarity in 3D structure to other omptin family members [24]; (ii) Pla can convert plasminogen to plasmin by limited proteolysis, and this activity was likely crucial for the increased lethality of Y. pestis during the course of evolution [37,38,39]; (iii) Pla pro-omptin is involved in the dissemination of Y. pestis into circulation and is known as one of the major virulence determinants of this pathogen [40,41,42]; (iv) this protein has both species-specific and genus-specific epitopes that were detected using a panel of monoclonal antibodies [43]; (v) Pla pro-omptin activation occurs at 37 °C, coinciding with the formation of truncated less-toxic tetra-acylated LPS, which is produced instead of highly toxic hexa-acylated LPS made by Y. pestis at 26 °C [44]. Importantly, the Pla pro-omptin is apparently involved in pathogen–host interaction following the induction of host immune response: a detectable level of the relevant antibodies to this antigen was found in the convalescent sera of human survivors of plague infection [45], in mice that survived experimental plague [46], and in the sera of animals and humans vaccinated with live plague vaccine (LPV, EV line NIIEG) [11,28,29,30].…”
Section: Discussionmentioning
confidence: 99%